The relationship between minority stress and biological outcomes: A systematic review - Flentje, Annesa (J Behav Med, 2019)
Sexual minority (non-heterosexual) individuals experience higher rates of physical health problems. Minority stress has been the primary explanatory model to account for this disparity. The purpose of this study was to identify in published research empirically established relationships between minority stress processes and biological outcomes and identify avenues for future research. The PubMed database was queried with search terms relevant to minority stress and a comprehensive list of physical and biological outcomes. To be included in the analysis, studies had to examine the relationship between minority stress and a biological outcome among sexual minority individuals. Those meeting inclusion criteria were coded for key variables including methodology used, positive and null results, participant characteristics, and specific minority stress processes and biological outcomes considered. In total, 26 studies met inclusion criteria. Studies tested relationships between specific minority stress processes including prejudice, expectations of prejudice, concealment of sexual orientation, and internalized stigma and multiple biological outcomes, such as overall physical health, immune response, HIV specific outcomes, cardiovascular outcomes, metabolic outcomes, cancer related outcomes, and hormonal outcomes. Studies included both analyses that detected this relationship (42% of analyses) and analyses that did not detect this relationship (58%). There is substantial evidence to support the relationship between minority stress and biological outcomes, yet additional research is needed to identify the measurements and outcomes that have the most rigorous and replicable results.